Benefit of the doubt: the buffering influence of normative contracts on the breach–workplace performance relationship. Issue 6 (26th March 2021) - Cregan, Christina; Kulik, Carol T.; Metz, Isabel; Brown, Michelle
Abstract: This study investigates the influence of employees' perception of managerial breach of the normative relational contract (i.e. the psychological relational contract at the group level) on workplace performance. Many employees in Australia are employed on a permanent or continuing basis and have normative relational contracts whose terms are embedded in human resource practices. We use normative relational contract theory to hypothesise that where there is a mutually recognised high-quality normative relational contract – a strong contract – the emotional bonds of loyalty that are developed by collective sense-making constrained negative reactions to breach. We also hypothesise that, where managers offer high-quality contract terms that are not recognised by employees, the failure to elicit loyalty means that breach has negative performance consequences. Panel data are obtained from a two-stage national, multi-source study of employees ( n = 1, 733) and senior human resource managers ( n = 57). Results from hierarchical moderator regression analyses support the hypotheses. They demonstrate that a strong normative relational contract 'buffers' employees' negative responses to breach.